DIRECTIONS AND TOOLS FOR THE DEVELOPMENT OF UKRAINE'S FOREIGN TRADE WITH EU COUNTRIES - MOTUZKA, Olena; SKYBA, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article highlights the importance of the active development of Ukraine's foreign trade with EU countries, with the aim of exiting and strengthening competitive positions in European markets and simultaneously reducing import dependence on European manufacturers. The purpose of the article is the scientific substantiation of the theoretical-methodical and applied foundations of the development of Ukraine's foreign trade with the EU countries, which will take into account a wide list of directions and instruments by which trade activity will be regulated and its promotion to foreign markets. The positive consequences of the creation of platforms for the development of Ukraine's foreign trade with EU countries have been identified. The weighty importance of the deepened and comprehensive free trade zone with European countries is proven and the expected results and negative changes that may occur in the deepening of European integration trade relations are listed. It is obvious that Ukraine, being in the current conditions, needs quick solutions, but looking at the expected post-war recovery, the issue of choosing directions and tools for the development of foreign trade with EU countries will be of critical importance. The obtained conclusions defined the toolkit, the implementation of which will ensure the achievement of the expected results in the development of Ukraine's foreign trade with the EU countries. The importance of developing the Strategy for the development of Ukraine's foreign trade with EU countries is emphasized and a set of target guidelines that must be followed in their implementation is highlighted. Important characteristics of the development of foreign trade relations are the institutional readiness of the national economy to adapt to globalization changes, to overcome hybrid threats, to strengthen competitive positions, which collectively forms the ability of domestic businesses to enter foreign markets, attract the necessary foreign financing of progressive projects, gain access to new technologies, etc.
Keywords: foreign trade; foreign economic relations; free trade zone; European integration